On-line Learning: Secondary Students’ First Experience - Tunison, Scott; Noonan, Brian (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
The development of on-line schooling may significantly affect the lives of both students and teachers. This study, conducted in a Canadian on-line secondary school, showed that students were generally satisfied with their first on-line learning experience, although they noted some serious deficiencies such as lack of training for the on-line class and ineffective use of key communication tools. We noted a contradiction between students’ appreciation of the flexibility and autonomy afforded them in the on-line environment and their struggle to manage that autonomy effectively. Un type de restructuration scolaire qui pourrait avoir un impact important sur la vie des élèves et des enseignants est le développement d’écoles en ligne. L’étude, qui a porté sur une école secondaire canadienne en ligne, révèle que les élèves étaient en règle générale satisfaits de leur expérience d’apprentissage en ligne bien qu’ils fassent état de graves lacunes, comme le manque de formation pour les cours en ligne et l’utilisation inefficace d’outils de communication clés. Les auteurs notent une contradiction entre le fait que les élèves aiment la latitude et l’autonomie que leur donne l’apprentissage en ligne et leur difficulté de gérer efficacement leur autonomie.